Pengaruh Kualitas Pelayanan dan Promosi Terhadap Kepuasan Pelanggan pada PT Stainlessindo Anugrah Karya di Kota Batam - realize Realize (JURNAL PUNDI, 2018)
Business competition in the Batam city nowadays can be said to be very strict because of the growing knowledge, culture and technology so that more competitors are opening a business in the same field. To overcome the tight competition in the marketing of stainless steel and iron work, one of the efforts must be done by the company is to implement the strategy of service quality and promotion to improve customer satisfaction. The purpose of this study is to determine the influence of service quality and promotion on customer satisfaction at PT Stainlessindo Anugrah Karya in Batam city individually and at the same time. This study method is by using descriptive analysis, data quality test, classical assumption test, multiple linear regression analysis, and hypothesis test. The results of this study indicate that the variable of service quality and promotion individually and simultaneously have a positive value and significance below the alpha level that has been assigned on customer satisfaction variable which the coefficient value of service quality has the most dominant contribution, so it can be concluded that the variable of service quality and promotion have positive and significant influence on customer satisfaction variable individually and simultaneously.